Thesis The Effect Of Warm Compresses On The Intensity Of Pain During The 1st Active Phase At Syekh Yusuf Gowa Hospital In 2020 - Nurul Ikawati (International Journal Of Health Science, 2024)
Childbirth is a physiological event in every woman's development into motherhood. This event can cause trauma because of the pain experienced, hot compresses are one method to overcome pain. The purpose of this study was to determine the effect of warm compresses on the intensity of labor pain during the 1st active phase at Syekh Yusuf Gowa Hospital.This type of research uses quantitative research with a quasi-experimental research design. The research design is one group pretest and postest design. Sampling technique with purposive sampling. The sample size was 30 respondents. Analysis using statistical test Mc Nemart test. The results showed that before the warm compress there were 8 people (26.7%) who experienced mild pain and 22 people (73.3%) who experienced severe pain. After being given warm compresses there were 8 (26.7%) who changed mild pain to severe and there were 22 (73.3%) people who changed from severe pain to mild pain. Based on the Mc Nemart test.then obtained the value of ρ = 0.000 < 0.05, it can be concluded the effect of warm compresses on the intensity of labor pain when 1 phase is active. The conclusion of this study is that warm compresses are effective in reducing the intensity of labor pain during the active phase I at Syekh Yusuf Gowa Hospital. And it is hoped that health workers or midwives can apply warm water compresses to reduce pain in maternity mothers